A Pemanfaatan TikTok Pada Kalangan Lansia di Kelurahan Sekarjaya Kabupaten Ogan Komering Ulu - Febriansyah, Dimas Rizky (Lentera Jurnal Pengabdian Masyarakat, 2024)
This research is motivated by one of the applications used by the elderly, namely the TikTok application, where TikTok has succeeded in attracting the interest of the elderly so that they have a sense of curiosity in searching for information and even participate in making short videos on the TikTok application. In general, TikTok is usually used by younger generation but also does not reduce the possibility of the elderly generation also using this media. The research method in this writing uses a qualitative descriptive method with new media theory and interviews that researchers conducted with 15 elderly informants in Sekar Jaya Village, Ogan Komering Ulu Regency, about how the elderly use TikTok social media. This research also explains the views of older people regarding negative content on social media. Based on the results of research conducted by researchers regarding the use of TikTok among the elderly in Sekar Jaya Village, Ogan Komering Ulu Regency, namely the use of TikTok as a useful medium in several aspects, namely First, as a medium for creativity by utilizing the features available on the TikTok application such as effects. Which is facilitated with videos, photos. Second, as an entertainment medium for the elderly to relieve boredom and fill their free time outside of their busy schedule as an elderly person by watching entertainment content on TikTok. Third, as an information medium it leads to the activities of elderly users looking for information conveyed by content creators using videos. This makes it easier for elderly people to get information by watching. Fourth, as a medium for shopping that leads to the activities of elderly users looking for products or goods by watching the results of ratings by other users, on TikTok there are many videos that promote MSME products.